From Huxley’s Soma to Smartphones: Exploration of Digital Dependency through the Lens of Brave New World - Khanom, Roxana (Literary Studies, 2025)
The research, From Huxley’s Soma to Smartphones: Exploration of Digital Dependency through the Lens of Brave New World examines the theme of digital dependency through the lens of Aldous Huxley's Brave New World. In the novel, Aldus Huxley presents a society that relies on drug soma to escape reality and maintain control mirroring our modern reliance on smartphones and digital technology. By drawing parallels between soma and contemporary digital devices, this study explores how technology influences our behavior, relationships, and sense of freedom. Huxley's dystopian vision serves as a powerful warning about the potential dangers of technological dependence. This research investigates how our constant connectivity and digital immersion can lead to a loss of individuality and critical thinking, much like the effects of soma in the novel. By analyzing the impact of digital media on our daily lives, this study aims to highlight the importance of balancing technological benefits with the preservation of human values. Through this critical analysis, we hope to provide insights into the challenges of digital dependency and encourage a more conscious engagement with technology